2021
DOI: 10.6007/ijarbss/v11-i8/10876
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Media Influencer towards Factors of Muslim Millennial Generation's Attitude into Halal Food Product Purchase in Malaysia

Abstract: Consumers have a tendency to reviews goods and services first before make a decision to buy. Consumer often to use the social platform to seek the information. In a current decade, the use of social media has in debate increased as a source to dig information. Social media influencers became part of the crucial medium in advertising goods and services to the consumers. The credible source of information by persuasive message can influence the purchasing behaviour of consumers towards goods and services. The gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…There is now a greater emphasis being placed on certification, regulation, and labeling in assuring Muslims of a product’s halal status, rather than on the personal trust between Muslims that underpinned traditional halal trade (Tayob, 2020a). Due to this, increasing numbers of Muslims have turned toward dedicated halal influencers on social media for help in navigating the increasingly complex rules and processes surrounding contemporary halal practices (Rahim et al, 2021; Rohman & Ulinnuha, 2022). Previous studies have found that these social media influencers shape the choice of halal products by Muslims (Fitriyani, 2021; Gunawan et al, 2021) and that they play an important role in educating the public on halal issues (Rohman & Ulinnuha, 2022).…”
Section: The Influence Of Presumed Media Influence Modelmentioning
confidence: 99%
“…There is now a greater emphasis being placed on certification, regulation, and labeling in assuring Muslims of a product’s halal status, rather than on the personal trust between Muslims that underpinned traditional halal trade (Tayob, 2020a). Due to this, increasing numbers of Muslims have turned toward dedicated halal influencers on social media for help in navigating the increasingly complex rules and processes surrounding contemporary halal practices (Rahim et al, 2021; Rohman & Ulinnuha, 2022). Previous studies have found that these social media influencers shape the choice of halal products by Muslims (Fitriyani, 2021; Gunawan et al, 2021) and that they play an important role in educating the public on halal issues (Rohman & Ulinnuha, 2022).…”
Section: The Influence Of Presumed Media Influence Modelmentioning
confidence: 99%
“…Influencer marketing has proven to be a highly effective way for businesses to build brand awareness, drive sales, and increase profits. The usage of social media influencers in the halal food industry has become increasingly popular in recent years (Rahim et al, 2021). Influencer marketing, where brands partner with individuals who have a large following on social media to promote their products, has become a widely used strategy in the halal food industry due to its ability to reach a large and engaged audience.…”
Section: Review Of Related Literature Social Media Influencers As Pro...mentioning
confidence: 99%